2004
DOI: 10.1158/1078-0432.ccr-03-0548
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of Different UGT1A1 Polymorphisms in Irinotecan-Induced Toxicity

Abstract: Purpose: We wanted to assess polymorphisms in the uridine diphosphoglucuronosyl transferase 1A1 (UGT 1A1) gene: the TATA box polymorphism and UGT 1A1 G71R and Y486D mutations in the coding sequence, the main mutations characterizing Gilbert's syndrome, as predictors of severe toxic event occurrence after irinotecan (CPT-11) administration. Therefore, we set up a rapid, sensitive, and reliable technique in routine practice to detect before CPT-11 treatment, the at-risk patients.Experimental Design: Seventy-five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
158
2
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 267 publications
(170 citation statements)
references
References 32 publications
7
158
2
3
Order By: Relevance
“…It was concluded that the UGT1A1*28 genotype correlates with severe neutropenia upon irinotecan treatment. Rouits et al (2004) obtained results similar to Innocenti et al with respect to neutropenia in 75 advanced CRC patients receiving CPT-11 þ 5-fluorouracil. Five of seven homozygous 7/7 patients had severe neutropenia, compared with 14 of 35 6/7 patients and only three of 31 6/6 patients.…”
Section: Ugt1a1 Polymorphisms and Cancer: Genotype-phenotype Correlationsupporting
confidence: 78%
“…It was concluded that the UGT1A1*28 genotype correlates with severe neutropenia upon irinotecan treatment. Rouits et al (2004) obtained results similar to Innocenti et al with respect to neutropenia in 75 advanced CRC patients receiving CPT-11 þ 5-fluorouracil. Five of seven homozygous 7/7 patients had severe neutropenia, compared with 14 of 35 6/7 patients and only three of 31 6/6 patients.…”
Section: Ugt1a1 Polymorphisms and Cancer: Genotype-phenotype Correlationsupporting
confidence: 78%
“…20,21 The clinical application of the genetic test for the UGT1A1*28 allele before irinotecan therapy has been in practice in the United States since 2005, based on a cumulative evidence supporting the significant association of this variant with severe irinotecan toxicity. 20,[22][23][24][25] The five most associated SNPs included rs4148323 (G4A, UGT1A1*6). Homozygotes of the UGT1A1*6 allele showed significantly high values in serum total bilirubin levels, supporting the evidence from earlier studies.…”
Section: Discussionmentioning
confidence: 99%
“…The number of such cases was too small to allow them to be treated as independent genotype classes, and the details of their expected effects are not clear enough 16 to warrant grouping them with other genotypes. In addition to (A(TA)nTAA), other UGT1A1 polymorphisms 17,18 and haplotypes 19 have been associated with bilirubin levels and Gilbert's syndrome. These may prove to be more effective biomarkers of hyperbilirubinemia risk than the promoter polymorphism alone.…”
Section: Max Grade P2mentioning
confidence: 99%